HUBUNGAN PENGETAHUAN, SIKAP IBU TERHADAP KEJADIAN STUNTING PADA BALITA DI BATU TANJUANG - Risnamawati Simamora; Liza Merianti; Kriscillia Molly Morita (Ensiklopedia Research and Community Service Review, 2025)
Abstract: Toddler growth remains a major public health concern, particularly in developing countries. Stunting is a condition characterized by impaired growth due to chronic malnutrition and recurrent infections occurring from the prenatal period until the age of 24 months, or during the first 1,000 days of life. A child is classified as stunted when their height-for-age is below -2 standard deviations. This study aimed to examine the relationship between mothers’ knowledge and attitudes toward the incidence of stunting among toddlers in Batu Tanjuang Village, the working area of Talawi Health Center, Sawahlunto City, in 2025. This quantitative research employed an analytic correlational design with a cross-sectional approach. The study was conducted from July to August 2025 with a total of 120 respondents, consisting of mothers with toddlers. The results showed that most toddlers had normal nutritional status (107 children; 89.2%), while 13 children (10.8%) were stunted. Regarding maternal knowledge, 70 respondents (58.3%) had moderate knowledge, 28 (23.3%) had good knowledge, and 22 (18.3%) had poor knowledge. In terms of attitudes, 70 respondents (58.3%) demonstrated moderate attitudes, 34 (28.3%) good attitudes, and 18 (13.4%) poor attitudes. Statistical analysis using Spearman’s rank correlation revealed a correlation coefficient of -0.477 with a p-value of 0.000, indicating a significant relationship with a moderate level of correlation. The study concluded that there is a significant relationship between mothers’ knowledge and attitudes and the incidence of stunting among toddlers in Batu Tanjuang. It is recommended that health promotion and educational programs be strengthened to improve mothers’ knowledge and attitudes in preventing stunting.Keywords: Stunting, Knowledge, Attitude.